Evaluating the role of a humanoid robot to support learning in children with profound and multiple disabilities - Hedgecock, Joseph; Standen, Penny J.; Beer, Charlotte; Brown, David; Stewart, David S. (Emerald, 2014)
Purpose The purpose of this paper is to identify ways teachers might employ a robot to achieve learning objectives with pupils with intellectual disabilities and potential outcome measures.